Distributed System with OPC UA and Industrial Internet for IEC 61499 Function Blocks - Rech R.P.* (2023)
© 2023 IEEE.This paper presents as a contribution an Industrial Internet system that enables the distributed execution of assembly and counting of industrial parts, using Function Blocks of Standard IEC 61499, which normally occurs in a centralized way. The Function Blocks run on microcontrollers that communicate via the OPC UA (Open Platform Communications Unified Architecture) protocol with the Factory I/O, a 3D factory simulation software, which operates on an end device. Experiments were carried out to measure the latency obtained with the OPC UA and the results confirm that the solution does not add delays that affect the application's operation.